2021
DOI: 10.3390/s21217332
|View full text |Cite
|
Sign up to set email alerts
|

UV Hyperspectral Imaging as Process Analytical Tool for the Characterization of Oxide Layers and Copper States on Direct Bonded Copper

Abstract: Hyperspectral imaging and reflectance spectroscopy in the range from 200–380 nm were used to rapidly detect and characterize copper oxidation states and their layer thicknesses on direct bonded copper in a non-destructive way. Single-point UV reflectance spectroscopy, as a well-established method, was utilized to compare the quality of the hyperspectral imaging results. For the laterally resolved measurements of the copper surfaces an UV hyperspectral imaging setup based on a pushbroom imager was used. Six dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The origin of their unique properties can be found in their extremely high surface-to-volume ratios and the way in which they interact with particular crystal faces. Applications cover a broad range of fields, such as in the sensing of various gases, 26–28 benzyl alcohol, 29 ethanol, 30 hydrogen, 31 glucose, 32,33 hydrogen sulphide, 34 and many other chemicals, as well as in catalysis 35 and photocatalysis, 36–38 batteries, 39,40 optoelectronics, 41 field emission, 42 supercapacitor applications, 43–45 broadband visible-light-driven surface-enhanced Raman scattering, 46,47 and others. 48–50…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of their unique properties can be found in their extremely high surface-to-volume ratios and the way in which they interact with particular crystal faces. Applications cover a broad range of fields, such as in the sensing of various gases, 26–28 benzyl alcohol, 29 ethanol, 30 hydrogen, 31 glucose, 32,33 hydrogen sulphide, 34 and many other chemicals, as well as in catalysis 35 and photocatalysis, 36–38 batteries, 39,40 optoelectronics, 41 field emission, 42 supercapacitor applications, 43–45 broadband visible-light-driven surface-enhanced Raman scattering, 46,47 and others. 48–50…”
Section: Introductionmentioning
confidence: 99%
“…The origin of their unique properties can be found in their extremely high surface-to-volume ratios and the way in which they interact with particular crystal faces. Applications cover a broad range of fields, such as in the sensing of various gases, [26][27][28] benzyl alcohol, 29 ethanol, 30 hydrogen, 31 glucose, 32,33 hydrogen sulphide, 34 and many other chemicals, as well as in catalysis 35 and photocatalysis, [36][37][38] batteries, 39,40 optoelectronics, 41 field emission, 42 supercapacitor applications, [43][44][45] broadband visible-light-driven surface-enhanced Raman scattering, 46,47 and others. [48][49][50] The role of CuO low-dimensional nanomaterials Similar to many other metal oxide nanostructures, forests of CuO nanowires demonstrate advanced properties that are particularly needed for many applications such as devices for field emission applications, 51 batteries, 52 supercapacitors, 53,54 and others.…”
Section: Introductionmentioning
confidence: 99%
“…Antony et al 22 used a HSI with a fibre bundle probe attached to detect corrosion on steel samples. Al Ktash et al 23 proposed a solution using UV HSI to characterise oxide layers on copper.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperspectral imaging and spectroscopic applications are widely used in industrial environments [ 5 , 6 , 7 , 8 , 9 , 10 ]. The importance of hyperspectral imaging is steadily growing in the textile industry.…”
Section: Introductionmentioning
confidence: 99%
“…The rarely used UV region showed interesting results despite the illumination not being optimal. Previously, our group reported a hyperspectral imaging setup for the UV spectral region, where this setup was used to distinguish between different pharmaceutical drugs [ 5 ], as well as for characterizing the oxide layers’ thickness and copper states on direct bonded copper [ 6 ]. The results clearly showed that a spectral imager based on pushbroom technology has many advantages in terms of achieving short UV operational wavelengths and a high spectral resolution.…”
Section: Introductionmentioning
confidence: 99%